Pengaruh Program Promosi Kesehatan Interaktif terhadap Peningkatan Pengetahuan HIV/AIDS pada Remaja - Alifiar, Ilham; Lutfhiani, Rani Putri; Saputri, Nadya Nasywa; Fauziah, Devi Sarah; Nuraisah, Ai; Nurlichan, Suci Rahayu; Ramdhani, Eki Muhammad; Wulandari, Ratna; Azzahra, Nurul Sulistia; Yunizar, Yuyun; Suryaman, Novita Deris; Anisa, Hilma Tri; Reiza Putri, Syakila Syalsa; Putri, Nadhira Alika; Laksana, Tiara Putri; Apriliani, Cici; Damayanti, Trisna Mutiara (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Introduction: HIV/AIDS remains a significant public health problem that requires effective prevention strategies, particularly through increasing knowledge among adolescents, who are considered a vulnerable group. Objective: This community service activity aimed to improve and evaluate adolescents’ knowledge of HIV/AIDS through interactive health promotion as an effort to support HIV/AIDS prevention. Method: This study employed a pre-experimental design using a one-group pre-test and post-test approach. A total of 18 adolescents participated as respondents. The intervention consisted of interactive health education delivered through presentations and posters containing information about HIV/AIDS, modes of transmission, prevention strategies, as well as myths and facts. Knowledge levels were measured using a questionnaire consisting of 10 multiple-choice questions. Data were analyzed using the Wilcoxon test. Result: The results showed an increase in the mean knowledge score from 74.44 in the pre-test to 96.11 in the post-test. Statistical analysis indicated a significant difference between pre-test and post-test scores (p = 0.001). Conclusion: Health promotion with the theme “Smart Teens Without Risk: Recognize, Prevent, and Control HIV/AIDS” was effective in improving adolescents’ knowledge about HIV/AIDS